Solubility and Scale-Up Potency of Norfloxacin-Urea Co-Crystal Prepared by Ultrasound-Assisted Slurry Co-Crystallization Method - Fikri Alatas; Dery Stiawan; Nur Achsan Al-Hakim (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2023)
Norfloxacin is an antimicrobial in treating urinary tract infections with low water solubility. This study aims to know the effect of norfloxacin-urea co-crystal formation on the solubility of norfloxacin and the potential for scale-up when prepared by ultrasound-assisted slurry co-crystallization method. Identification of the screening result of the norfloxacin-urea (1 : 1) co-crystal formation by a wet grinding method using an ethanol-acetone (1 : 1) solvent mixture was performed by powder X-ray diffractometer (PXRD). The ultrasound-assisted slurry co-crystallization method was used for co-crystal formation with five-fold the weight of norfloxacin and urea than the wet grinding method. The co-crystal product prepared by the ultrasound-assisted slurry co-crystallization method was observed for its crystal morphology and characterized by PXRD and differential scanning calorimeter (DSC). Solubility and dissolution tests in water and acetate buffer solution pH 4.0 were used to evaluate the physicochemical properties. Identification of co-crystal screening by PXRD revealed the formation of norfloxacin-urea co-crystal. The PXRD pattern of the norfloxacin-urea co-crystal product prepared by the ultrasound-assisted slurry co-crystallization method was similar to the wet grinding method. Norfloxacin-urea co-crystal has a different melting point and crystal morphology from pure norfloxacin and urea. The solubility and dissolution rate of norfloxacin-urea co-crystal was higher in water and not significantly different in acetate buffer solution pH 4.0 compared to pure norfloxacin. This study showed that the norfloxacin-urea co-crystal formation could enhance the solubility of norfloxacin in water and had the potential for scale-up when prepared using the ultrasound-assisted slurry co-crystallization method.